Harmonic Current Suppression of Dual Three-Phase Permanent Magnet Synchronous Motor with Improved Proportional-Integral Resonant Controller - Lei Chen; Min Chen; Bodong Li; Xinnan Sun; Feng Jiang (Energies)
The impedance of the harmonic plane in a dual three-phase permanent magnet synchronous motor (DTP-PMSM) is very low, meaning that even small harmonic voltages can induce significant harmonic currents, particularly at the fifth and seventh harmonic frequencies. These harmonic currents can severely degrade system performance and increase losses. To address this issue, the mechanism of harmonic current generation due to non-sinusoidal back electromotive force (EMF) and inverter nonlinearity is first analyzed. Then, to overcome the challenge of excessive controllers in traditional harmonic suppression strategies, a rotational coordinate transformation of the harmonic plane current is employed, which unifies the controllers and reduces their number. Since traditional proportional-integral resonant (PIR) controllers are ineffective at a high-speed region, an improved PIR controller for the harmonic plane is proposed. This controller incorporates digital delay compensation, phase compensation, and discretization correction to minimize the deviation between the discretized resonant frequency and the actual frequency. These enhancements enable harmonic suppression across the entire speed range and under varying load conditions, significantly reducing harmonic currents. Finally, the proposed harmonic current suppression strategy is experimentally validated.